Relationship Between Amyloid-β Deposition and Blood–Brain Barrier Dysfunction in Alzheimer’s Disease - Wang, Dong; Chen, Fanglian; Han, Zhaoli; Yin, Zhenyu; Ge, Xintong; Lei, Ping (Frontiers in Cellular Neuroscience, 2021)
Amyloid-β is the predominant pathologic protein in Alzheimer’s disease. The production and deposition of Aβ are important factors affecting AD progression and prognosis. The deposition of neurotoxic Aβ contributes to damage of the blood–brain barrier. However, the BBB is also crucial in maintaining the normal metabolism of Aβ, and dysfunction of the BBB aggravates Aβ deposition. This review characterizes Aβ deposition and BBB damage in AD, summarizes their interactions, and details their respective mechanisms.